2007
DOI: 10.1071/pc070189
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fire and dogs on Koalas at Port Stephens, New South Wales, using population viability analysis

Abstract: The Port Stephens Koala Phascolarctos cinereus population has been regarded as one of the strongholds for Koalas in New South Wales. This study applied population viability analysis to investigate the impact of fire and predation by dogs on the viability of the local population. The rapid decline of the modelled Koala population under basic assumptions throws the assumed security of such large populations into question. In all the modelled management scenarios, reducing mortality had more influence than any ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 32 publications
(49 reference statements)
3
60
0
1
Order By: Relevance
“…Our models identified that, between 1995 and 2005, the landscape matrix progressively became more hostile to koalas moving between fragments. Slight increases in the death rate of adult breeding females can have a major impact on population survival, as has been shown in other NSW coastal populations (Lunney et al , 2007. Given this finding, it becomes increasingly important to manage mortality factors on individual koalas, such as from dogs, cars and fire.…”
Section: Land-use Change In the Eden Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our models identified that, between 1995 and 2005, the landscape matrix progressively became more hostile to koalas moving between fragments. Slight increases in the death rate of adult breeding females can have a major impact on population survival, as has been shown in other NSW coastal populations (Lunney et al , 2007. Given this finding, it becomes increasingly important to manage mortality factors on individual koalas, such as from dogs, cars and fire.…”
Section: Land-use Change In the Eden Regionmentioning
confidence: 99%
“…Household density represents the density of human population in the region and has an indirect impact on koala populations because it is associated with the density of domestic dogs and road traffic, which directly threatens koala populations (Melzer et al 2000;Lunney et al 2007; Commonwealth of Australia 2009).…”
Section: Climate and Land-use Changementioning
confidence: 99%
“…Koalas are considered a vulnerable species in parts of Australia due to rapid population decline. Whilst the contraction of populations is primarily attributed to the impacts of urbanization (Lunney et al, 2007;de Oliveira et al, 2014), disease from pathogens such as Chlamydia pecorum may play an important role .…”
Section: Introductionmentioning
confidence: 99%
“…Local koala populations face several threats, including loss and fragmentation of habitat (Melzer et al 2000;McAlpine et al 2006a;McAlpine et al 2006b), car strikes and dog attacks (Dique et al 2003;Lunney et al 2007), and disease, which can lead either to death or infertility (Gordon et al 1990;Hanger and Loader 2009). Koalas are susceptible to climatic extremes, particularly heatwaves and droughts, which also affect the quality of nutrients and moisture available in their diet (Cork and Braithwaite 1996;Moore and Foley 2000).…”
Section: Introductionmentioning
confidence: 99%